The differing status of reconstruction in Trans-Himalayan and Indo-European - Hill, Nathan (My University, 2019)
The replies to Fellner and Hill (this volume) present the practice of historical linguistics in the study of the Trans-Himalayan family as on the trail our Indo-European forbears blazed. The replies further present “word families” and “allofams” as beacons that light this path; we disagree. Our respondents overlook the different status of reconstructions in the two families. Research at the subgroup level that they point to as Neogrammarian implements a formalist approach to reconstruction, which, fine as far as it goes, lacks the sophistication of reconstructions in more mature disciplines. Not appreciating the different status of reconstruction in the two families, our respondents exaggerate the extent to which Indo-European evinces “word family”-like phenomena and present allofams as more synchronically plausible than they are.
PUBLISHED
Keywords: Reconstruction; Trans-Himalayan; Indo-European; Methodology; Word families